Specific spin-labeling of transfer ribonucleic acid molecules. - Caron, M (1976)
The spin labels anhydride (ASL), bromoacetamide (BSL) and carbodiimide (CSL) were used to label selectively tRNAGlu, tRNA fMet and tRNAPhe from E. coli. The preparation and characterization of the sites of labeling of eight new spin-labeled tRNAs are described. The sites of labeling are: s2U using ASL, BSL and CLS and tRNAGlu; s4U using ASL and BSL on tRNAfMet and tRNAPhe; U-37 with CSL on tRNfMet; U-33 with CSL on tRNAPhe. The rare base X at position 47 of tRNAPhe has been acylated with a spin-labeled N-hydroxysuccinimide (HSL). The 3'end of unfractionated tRNA molecules has been chemically modified to a morpholino spin-labeled analogue (MSL). Their respective e.s.r. spectra are reported and discussed.